A systematic review and recommendations on the use of plasma EBV DNA for nasopharyngeal carcinoma. (August 2021) - Lee, Anne W.M.; Lee, Victor H.F.; Ng, Wai-Tong; Strojan, Primož; Saba, Nabil F.; Rinaldo, Alessandra; Willems, Stefan M.; Rodrigo, Juan P.; Forastiere, Arlene A.; Ferlito, Alfio
Abstract: Introduction: Nasopharyngeal carcinoma (NPC) is an endemic malignancy in Southeast Asia, particularly Southern China. The classical non-keratinising cell type is almost unanimously associated with latent Epstein–Barr virus (EBV) infection. Circulating plasma EBV DNA can be a useful biomarker in various clinical aspects, but comprehensive recommendations and international guidelines are still lacking. We conducted a systematic review of all original articles on the clinical application of plasma EBV DNA for NPC; we further evaluated its strengths and limitations for consideration as standard recommendations. Methods: The search terms 'nasopharyngeal OR nasopharynx', and 'plasma EBV DNA OR cell-free EBV OR cfEBV' were used to identify full-length articles published up to December 2020 in the English literature. Three authors independently reviewed the article titles, removed duplicates and reviewed the remaining articles for eligibility. Results: A total of 81 articles met the eligibility criteria. Based on the levels of evidence and grades of recommendation assessed, it is worth considering the inclusion of plasma EBV DNA in screening, pre-treatment work-up for enhancing prognostication and tailoring of treatment strategy, monitoring during radical treatment, post-treatment surveillance for early detection of relapse, and monitoring during salvage treatment for recurrent or metastatic NPC. One major limitation is the methodology of measurement requiring harmonisation for consistent comparability. Conclusions: The current comprehensive review supports the inclusion of plasma EBV DNA in international guidelines in the clinical aspects listed, but methodological issues must be resolved before global application. Highlights: Plasma Epstein–Barr virus DNA has been the most reliable and accurate marker in nasopharyngeal carcinoma management. We provide evidence-based recommendations on its use in various clinical settings. We support its inclusion in international guidelines in the aspects listed. Limitations and methodological issues must be resolved before its global application.